A new species of freshwater crab of the genus neostrengeria pretzmann, 1965, from meta department, colombia (crustacea: decapoda: pseudothelphusidae) (2011)
A new species of frfreshwater crab of the pseudothelphusid genus Neostrengeria Pretzmann, 1965, is described and illustrated. This discovery means the genus now contains 25 species, all of which are endemic to the Eastern Andes of Colombia. The new species is distinguished fr om their congeners primarily by the morphology of the first male gonopod, particularly by the shape of the accessory lobe, outline of apex and mesial lobe.